H3K56 acetylation regulates chromatin maturation following DNA replication - Shoufu Duan; Ilana M. Nodelman; Hui Zhou; Toshio Tsukiyama; Gregory D. Bowman; Zhiguo Zhang (Nature Communications)
Abstract Following DNA replication, the newly reassembled chromatin is disorganized and must mature to its steady state to maintain both genome and epigenome integrity. However, the regulatory mechanisms governing this critical process remain poorly understood. Here, we show that histone H3K56 acetylation (H3K56ac), a mark on newly-synthesized H3, facilitates the remodeling of disorganized nucleosomes in nascent chromatin, and its removal at the subsequent G2/M phase of the cell cycle marks the completion of chromatin maturation. In vitro, H3K56ac enhances the activity of ISWI chromatin remodelers, including yeast ISW1 and its human equivalent SNF2h. In vivo, a deficiency of H3K56ac in nascent chromatin results in the formation of closely packed di-nucleosomes and/or tetra-nucleosomes. In contrast, abnormally high H3K56ac levels disrupt chromatin maturation, leading to genome instability. These findings establish a central role of H3K56ac in chromatin maturation and reveal a mechanism regulating this critical aspect of chromosome replication.